Antimicrobial Activity of Extracts from Native Plants of Temperate Australia - Wigmore, Sarah M.; Naiker, Mani; Bean, David C. (Pharmacognosy Communications)
Introduction: Significant effort has been invested in looking at the antimicrobial activity of plant extracts from tropical regions of Australia, with less interest in those from more temperate environments. We sought to redress this imbalance by examining antimicrobial activities of extracts from native plants of Victoria. Methods: Sixteen plant samples were obtained around the Ballarat region of Victoria. Plant material was desiccated, ground and extracted with methanol at room temperature. Methanol extracts were subsequently dissolved in water, filtered and freeze dried. Extracts were dissolved in water and their activity determined against eight bacterial species. Plant extracts that showed appreciable antibacterial activity in the initial antimicrobial screen were examined further with both their MICs and MBCs determined. Results: Ten of the sixteen plant extracts showed antimicrobial activity. Extracts of Eucalyptus, Melaleuca, Prostanthera and Westringia were particularly active with MICs as low as 0.25 mg/ml against organisms including P. aeruginosa and S. aureus. Conclusion: The current study demonstrates the antimicrobial activity of plant extracts from temperate Australia. These may serve as precursors for future chemotherapy agents.
Keywords: Antibacterial Activity; Melaleuca; Prostanthera; Westringia; P. aeruginosa.